Development of Physical Fitness of Wrestlers - Keldiyorov Shukhrat Ergashovich (Zien Journals, 2023)
This article analyzes the work on the development of national sports and develops proposals and recommendations for the development of wrestling sports.
Keywords: physical education; sports; wrestling; national sports